PERANAN LINGKUNGAN SEKOLAH TERHADAP PENGUATAN KARAKTER PEDULI LINGKUNGAN SISWA SMAN 111 JAKARTA - Anastya Zalfa, Anastya Zalfa; Shobihah, Alya; Fadhil, Abdul (Universitas Tanjungpura, 2022)
This study aims to describe the role of the school environment in strengthening the environmental care character of students at SMA Negeri 111 Jakarta. This type of research is a qualitative approach with descriptive research methods. Data collection techniques in this study used interviews, observation, and documentation. The validity of the data in this study uses triangulation of sources and techniques. Data analysis used the interactive model of Miles and Huberman with three stages, namely data reduction, data display, decision making and verification which were presented in a qualitative descriptive manner. The results of this study prove that the role of the school environment in strengthening the character of caring for the environment is manifested in several ways including, (1) providing exemplary habituation, (2) habituation of maintaining cleanliness and environmental sustainability, (3) the availability of supporting facilities including the provision of cleaning equipment, garbage disposal sites. , toilets and clean water as well as slogans or posters caring for the environment in various corners of the school, and (4) support the Adiwiyata program by holding clean Fridays, a waste bank and making compost.